Reality Counseling for Drug Depriants in the Adjustment Period in Prices - Rizal, Syamsul (Corolla International Conference, 2022)
The mix method technique is used in this study, which involves data gathering and integration of quantitative and qualitative data in one study to give a more thorough understanding. The goal of this study is to assist new convicts, particularly those implicated in drug cases, in adjusting to and being responsible in a new setting, namely LAPAS Class II A Curup, Rejang Lebong Regency. Based on the context of the problem, questions such as how to adjust to new inmates, particularly drug cases in Class II A Curup LAPAS, before receiving counseling services, how reality counseling can alleviate the anxiety experienced by new inmates, particularly drug inmates in Class II A Curup, and how to adjust to new inmates following the implementation of reality counseling can be posed. The outcomes of reality counseling implementation have made people especially supported by medications more clever in adjusting to the environment they experience. Because the adjustment to the new environment is not only transitory but fresh adjustments are also required when they encounter a new circumstance.